2003
DOI: 10.1007/s10333-002-0007-7
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of adsorption and movement by predicting ammonia nitrogen concentrations in paddy percolation water

Abstract: We noted that ammonia nitrogen was not adsorbed by the cultivated layers of highly permeable paddy fields during the initial fertilization period, but reached the lower layers relatively early. In our study, we considered an exponential equation from an aqua-environmental perspective with the goal of obtaining good growth of rice plants in order to estimate the concentrations and integrated volume of ammonia nitrogen accompanying paddy percolation. Using this exponential equation, we were able to derive a rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…44, 26.26, 9.79, 9.59, 10.34, and 23.30 were thus determined for the soil depth ranges of 0-10, 10-20, 20-30, 30-40, 40-50, and 50-60 cm, respectively. The maximum value of retardation factor appears in the soil at the medium depth of 10-20 cm, which shows that this layer has the strongest sorption capacity for NH 4 + -N. Ishikawa et al (2003) reported similar finding about NH 4 + -N adsorption relating to constant area with the soil particles, when they studied the adsorption on NH 4 + -N in paddy soil percolation water.…”
Section: Adsorption Isothermssupporting
confidence: 59%
See 1 more Smart Citation
“…44, 26.26, 9.79, 9.59, 10.34, and 23.30 were thus determined for the soil depth ranges of 0-10, 10-20, 20-30, 30-40, 40-50, and 50-60 cm, respectively. The maximum value of retardation factor appears in the soil at the medium depth of 10-20 cm, which shows that this layer has the strongest sorption capacity for NH 4 + -N. Ishikawa et al (2003) reported similar finding about NH 4 + -N adsorption relating to constant area with the soil particles, when they studied the adsorption on NH 4 + -N in paddy soil percolation water.…”
Section: Adsorption Isothermssupporting
confidence: 59%
“…According to Ishikawa et al (2003), NH 4 + -N concentrations in water percolating paddy fields will decrease as the percolation rates decrease, which means that a lower percolation rate might increase the contact time and as a result enhance the soil's ability to absorb NH 4 + -N. Jellali et al (2010) reported similar findings when they studied ammonium adsorption by sandy soil in fixed bed columns. To our knowledge, there is no such a research about ammonia adsorption effects of irrigation flow rates on sandy soil using these models.…”
Section: Introductionmentioning
confidence: 88%
“…Concentrations of total nitrogen in irrigation water, rainfall, and standing water were measured with a total nitrogen analyzer (TN-301P, Anatec Yanaco, Kyoto, Japan). Percolating water below 20 cm depth were sampled by soil water samplers (DIK-8390, Daiki Rika Kogyo Ltd., Saitama, Japan), and the concentrations of nitrate-nitrogen and nitritenitrogen were measured by high performance liquid chromatography (L-6000, Hitachi, Ltd., Tokyo, Japan) (Ishikawa et al, 2003). Concentrations of sulphate, fluoride and chloride were also determined.…”
Section: Cultural Details (1) Winter Cropsmentioning
confidence: 99%
“…Efficient resource use and least harmful effects on environments are needed in urban agriculture (e.g. concentration of nitrate in percolating water, Ishikawa et al, 2003). Higher productivity is also desirable, in spite of the fact that current rice yield in urban areas, e.g.…”
mentioning
confidence: 99%
“…An important and apparent function of paddy field is its capability of flood retention during the typhoon and monsoon seasons (Nakanishi, 2004;Unami and Kawachi, 2005). Other functions of paddy culture include recharge of groundwater (Greppi, 2004), air temperature cooling (Saptomo et al, 2004;Yokohari et al, 1997Yokohari et al, , 2001, removal of pollutants in irrigation water (Ishikawa et al, 2003;Nakasone, 2003), providing habitat for inhabitants (Fukuda et al, 2006), aesthetic landscape, and facilitating religious/cultural activities. Many of these functions have been experienced or practiced for many generations.…”
Section: Introductionmentioning
confidence: 99%